The Preschool Teachers' Attitudes About Education of Multiculturalism - Miray Özözen Danacı; Nuray Eran; Zeynep Çetin; Özge Pınarcık; Muhammed Bahtiyar (Hacettepe University, 2016)
Multicultural education; ethnicity, religion, race, language, gender, where cultural properties due to differences such as the living area, to reduce identity conflicts and power sooner quinidine, society, philosophy of education that appeal to different cultural characteristics and be reflected in the formal education of the application and based on democratic values, to promote cultural diversity equality training which is defined as a mixed school climate.This study was conducted to determine the pre-school teachers in multiculturalism and cognitive levels of knowledge and attitudes of multicultural education. The study population consisted of teachers in pre-school located in Düzce. The sample of the study in Düzce province in formal kindergarten and kindergarten assistants, including 5 men and 86 women constitute 91 pre-school teachers. Joseph research within the framework of quantitative research methods Ponterotto G. (1998) led a group of researchers developed by the Multicultural Education Teacher Attitudes (OCTO) is used. Research has established formal working group of kindergarten and pre-school teachers working in kindergarten. The study was carried out with the teacher. The scale used in this study, Cronbach alpha reliability coefficient of .74 bulunarak as is provided for translation and language validity. Factor analysis showed that the scale of the one-dimensionality of supported theoretically predicted. Age according to the result, graduated region where the school is located, where the school their seniority and job place and according to the cultural structure of the occurrence of settlement of prior training for the various variables was examined whether there is a difference. As a result, the location of the school they graduated teachers, seniority, school, depending on whether they work in the province or district was found that differences in the approach to multicultural education.